TINJAUAN PEMBUATAN INDEKS UNIT REKAM MEDIS DI RUMAH SAKIT DAERAH KABUPATEN PEMALANG - Nugeraheni, Apriliarum; Fani, Tiara (VISIKES: Jurnal Kesehatan Masyarakat, 2023)
One of the regional hospitals in Pemalang Regency has not compiled an Outpatient Disease Index and the process of making other indexes is still manual. The study aims to determine the process of making an index of Medical Record Units at Pemalang Regency Regional Hospitals in 2022. This research is qualitative research with a case study approach. Data collection through semi-structured interviews with indexing officers and observations on the index table design. Analysis of interview results and observations using synthesis analysis. The results of this study show that the data sources for the RI and RJ disease index, patient index, surgery index, doctor index, and death index made by hospitals are taken from medical record documents, while the data sources for the Patient Index and Inpatient Index are taken from SIMRS. Index data processing is done manually (inpatient disease index, outpatient index, doctor index, surgery index, and mortality index) and electronically (patient index). The use of SIMRS in Unit Indexing is not fully used because most of the process is done manually (Microsoft Excel), except for the Patient Index. Suggestion, To improve the quality of hospital services, the hospital should evaluate the performance of medical personnel in the ward in inputting resume data of patients returning home both in SIMRS and in DRM. In addition, improving the features or functions of SIMRS in order to collect, process, and present all index data (Inpatient Disease Index, Outpatient Index, Patient Index, Operation Index, Doctor Index, and Death Index) needed by the hospital.